Comprehensive typology of rural settlements in the Kaliningrad region - Ivan S. Gumenyuk; Lidia G. Gumenyuk (Baltic Region)
The rural settlement system of the Kaliningrad region, comprising 1,075 localities, is characterised by compactness, high economic development and a predominance of small rural settlements. From 2010 to 2024, the region’s rural population increased from 210 to 235 thousand people. Simultaneously, the number of large rural settlements is growing in the western part of the region, while a stable trend of demographic decline persists among small rural settlements in the eastern part. Using statistical data, along with quantitative data from previous studies, open sources and field research materials, the authors developed a comprehensive typology of Kaliningrad region’s rural settlements. The typology classifies settlements according to demographic factors, spatial location, availability of social infrastructure, tourism and recreation facilities and agricultural enterprises of various types. The research methods encompassed tools for gathering, processing and analysing primary data, including statistical, cartographic and comparative-geographical techniques. As a result, 18 types of rural settlements were identified in the Kaliningrad region, each characterised by a unique trajectory of socio-economic and demographic development. These distinctions should be considered when designing and implementing spatial development programmes and projects at local or regional levels. The research results are presented in cartographic and tabular formats.